2015
DOI: 10.2169/internalmedicine.54.4283
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Prognostic Factors in Patients with Rheumatologic Diseases Admitted to the ICU

Abstract: Objective To assess the outcomes in a large cohort of patients suffering from rheumatic diseases admitted to the ICU of a tertiary university medical center. Methods A retrospective chart analysis was performed in 108 patients suffering from various rheumatic diseases and the outcomes, including morbidity and mortality, were assessed in relation to the underlying diseases, treatments and complications. Results Overall, 48 patients with rheumatoid arthritis, five patients with spondyloarthritis, 14 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
24
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 27 publications
(26 reference statements)
8
24
2
2
Order By: Relevance
“…Renal replacement therapy was frequently used for worsened liver failure and renal disease among comorbidities and was increased in the nonsurvivors of the 30-day mortality group. Together with the ndings from previous reports [12,54], our data indicate that ICU patients requiring renal replacement therapy showed poorer prognosis. Previous studies reported that other organ replacement therapies, including mechanical ventilation and vasopressors, were associated with a higher mortality in the ICU population [12,17,47,55,56].…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Renal replacement therapy was frequently used for worsened liver failure and renal disease among comorbidities and was increased in the nonsurvivors of the 30-day mortality group. Together with the ndings from previous reports [12,54], our data indicate that ICU patients requiring renal replacement therapy showed poorer prognosis. Previous studies reported that other organ replacement therapies, including mechanical ventilation and vasopressors, were associated with a higher mortality in the ICU population [12,17,47,55,56].…”
Section: Discussionsupporting
confidence: 84%
“…Together with the ndings from previous reports [12,54], our data indicate that ICU patients requiring renal replacement therapy showed poorer prognosis. Previous studies reported that other organ replacement therapies, including mechanical ventilation and vasopressors, were associated with a higher mortality in the ICU population [12,17,47,55,56]. By contrast, the present study did not nd any difference in the 30-day mortality groups probably because our study only included RA patients and did not include those with other collagen diseases, such as systemic lupus erythematosus, dermatomyositis, Sjögren's disease, progressive systemic sclerosis, mixed connective tissue disease, or vasculitis.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations